A Novel Controllable Reactor Technology for Reactive Power Compensation of Electrified Railways - 张宇; 李江红; 陈乔夫; 王坚; 谭娟 (Kongzhi Yu Xinxi Jishu)
A multi-winding reactor, the secondary windings of which connecting anti-parallel thyristors and voltage- source inverter (VSI) respectively, can obtain reactance varying in a wide range continuously with the thyristors′ stepping switching and VSI controlling. With parallel operation of the controllable reactor and fixed capacitor branches, reactive power of traction substations can be regulated automatically according to dynamic loading for increasing power factor. Simulating and experimental results validate the advantages of the presented reactor such as fast response, high compensating precision and low harmonic output etc.